RELIGIOUS HATE SPEECH vs PEACEFUL CO-EXISTENCE: A Socio-Legal Review - S, Suvidutt M. (Journal of Dharma, 2022)
Hate speech is viewed in the context of institutionalised prejudice and a community’s eventual marginalisation - be it politically, socially, economically, religiously, culturally, racially, sexually, etc. The best method to combat religious hate speech in a democratic setting like India is to preserve, embrace, and practise ‘constitutional values’. It is pointless to promote new laws that prohibit or restrict freedom of expression in order to avert attacks on religion. The Hon’ble Supreme Court of India has extensively commented on religion, secularism, and hate speech. The Sustainable Development Goal (SDG) 16 addresses hate speech by urging the development of peaceful and inclusive communities, universal access to justice, and effective, responsible, and inclusive institutions at all levels. The United Nations’ efforts to make the SDGs a reality also contribute to fighting the issue of hate speech as part of accomplishing these interrelated goals that assist in establishing a peaceful and resilient society. This paper elucidates the heated arguments involved in the hate speech that is antithetical to secularism, inclusive societies, and sustainable development.